State and Trends of Carbon Pricing 2018 - World Bank; Ecofys (Washington, DC: World Bank, 2018)
The State and Trends of Carbon Pricing series reflects on the growing momentum for carbon pricing worldwide. It targets the wide audience of public and private stakeholders engaged in carbon pricing design and implementation.